PERJAMUAN KUDUS BAGI ANAK DALAM GEREJA METHODIST - Samosir, Nettina; Parhusip, Mangatas (Majalah Ilmiah METHODA, 2023)
This study aims to find out about the attitude of the Methodist Church in involving children to receive the elements of the communion. The Holy Communion is one of the two sacraments recognized by Protestant Christian churches. This Holy Communion is a direct command from the Lord Jesus to be carried out by His churches on this earth. This can be seen from the words of Jesus who stated "Do this in remembrance of me". According to John Wesley, communion is a suggestion of grace that God has given to every human being. That gift was given by God to everyone by God's will, everyone can receive it because that gift is God's love for humans through Jesus Christ who sacrificed himself as a way of salvation for mankind. According to John Wesley communion is a universal means of grace, therefore children may participate in the communion.